2022
DOI: 10.1002/ajh.26680
|View full text |Cite
|
Sign up to set email alerts
|

Erythroferrone contributes to iron mobilization for embryo erythropoiesis in iron‐deficient mouse pregnancies

Abstract: Erythroferrone (ERFE) is an erythroblast‐secreted regulator of iron metabolism. The production of ERFE increases during stress erythropoiesis, leading to decreased hepcidin expression and mobilization of iron. Pregnancy requires a substantial increase in iron availability to sustain maternal erythropoietic expansion and fetal development and is commonly affected by iron deficiency. To define the role of ERFE during iron‐replete or iron‐deficient pregnancy, we utilized mouse models expressing a range of ERFE le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Mechanistic studies in mouse models showed that ERFE knockout mice are fertile (72) and that maternal hepcidin is appropriately suppressed, indicating that ERFE is not the physiological pregnancy hepcidin suppressor. In iron-deficient dams, ERFE deficiency had only very minor effects on maternal erythropoiesis (115). Thus, maternal ERFE may be a useful marker of iron deficiency anemia in pregnancy but does not strongly regulate maternal iron homeostasis.…”
Section: Inflammation and Hepcidin During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistic studies in mouse models showed that ERFE knockout mice are fertile (72) and that maternal hepcidin is appropriately suppressed, indicating that ERFE is not the physiological pregnancy hepcidin suppressor. In iron-deficient dams, ERFE deficiency had only very minor effects on maternal erythropoiesis (115). Thus, maternal ERFE may be a useful marker of iron deficiency anemia in pregnancy but does not strongly regulate maternal iron homeostasis.…”
Section: Inflammation and Hepcidin During Pregnancymentioning
confidence: 99%
“…In nonanemic human and rodent pregnancies, serum ERFE levels are not significantly affected by pregnancy status (138). However, in mouse models of iron-restricted or iron-deficient pregnancy with ensuing anemia, maternal ERFE levels are significantly elevated (111,115). Elevated maternal ERFE has also been reported in anemic human pregnancies (30).…”
Section: Inflammation and Hepcidin During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…This does not exclude a role for ERFE in pregnancy, as circulating levels are normally very low, with accurate detection using ELISA only possible in conditions of extreme erythroid stimulation, such as in β-thalassemia [ 35 ]. A study showing that pregnant mice lacking ERFE produce smaller erythrocytes—consistent with iron deficiency—supports a role for this hormone in the maintenance of erythroid iron supply during pregnancy [ 36 ]. ERFE suppresses hepcidin by binding to BMP6 and preventing the activation of the SMAD signaling pathway [ 37 ]; however, the level required for suppression likely depends on the amount of BMP6 present.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 54 However, in animal studies of nonanemic pregnancies, ERFE did not appear to play a major role in maternal and fetal iron homeostasis. 55 Finally, in case of maternal iron deficiency anemia, the common homeostatic regulatory mechanisms of iron uptake and transfer to the fetus are engaged and possibly regulated more by fetal than by maternal iron demands. 56 Maternal and fetal hepcidin both decrease further with iron deficiency anemia to promote iron availability and transfer to the fetus.…”
Section: Anemia In Healthy Pregnancymentioning
confidence: 99%